2004
DOI: 10.1890/1540-9295(2004)002[0183:ppaibp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Parasites, pathogens, and invasions by plants and animals

Abstract: Biological invasions cause billions of dollars in economic damage each year and are a serious threat to native biodiversity. Introduced animals and plants may escape 75% or more of the parasite and pathogen species from their native range. While they do accumulate novel parasite species from their new location, this number is generally only a fraction of the number lost. Individual plants and animals are also generally less frequently infected (prevalence minus percent individuals infected) in introduced compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
129
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(131 citation statements)
references
References 37 publications
1
129
0
1
Order By: Relevance
“…Some studies have shown that species introduced into a novel environment often lose their own parasites during the course of a new population establishment (Torchin et al 2003; Torchin and Mitchell 2004) but also encounter and accumulate parasites that occur in newly colonized areas. In addition, there may be a significant probability of raccoons introducing some new parasite species, recorded previously in individuals from North America, into European ones.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that species introduced into a novel environment often lose their own parasites during the course of a new population establishment (Torchin et al 2003; Torchin and Mitchell 2004) but also encounter and accumulate parasites that occur in newly colonized areas. In addition, there may be a significant probability of raccoons introducing some new parasite species, recorded previously in individuals from North America, into European ones.…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular interest for invasive plants undergoing range expansion, as the interactions between a host plant and its enemies can be an important determinant of future spread. The Enemy Release Hypothesis is a well-established explanation for the success of many invasive plants, whereby the invader benefits from reduced enemy pressure in the invaded range as a consequence of leaving behind species-specific herbivores and pathogens during the invasion process (Elton, 1958;Keane & Crawley, 2002;Torchin & Mitchell, 2004).…”
mentioning
confidence: 99%
“…More information on the number, identity, distribution, and pathogenicity of parasites would be needed to enable, or prioritize, assessment of novel parasites at the hazard-identification stage and to reduce the number of parasites requiring assessment. Research on parasite loss and persistence in non-native species (Torchin et al 2003;Torchin & Mitchell 2004;MacLeod et al 2010) and wild animals in trade (Smith & Daszak 2009) may suggest which parasite groups are most likely to be source hazards given their ability to persist in translocated populations. So far, such research has identified only host factors that are strongly associated with parasite persistence (Macleod et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We defined parasites as infectious agents, including viruses, bacteria, fungi, protozoa, helminths, and ectoparasites. Some translocated organisms have fewer parasites than others, and therefore may have higher fitness (Torchin et al 2003;Torchin & Mitchell 2004) than conspecifics in the organism's source range. For example, House Sparrows (Passer domesticus) introduced to North America from Europe have fewer genera and species of parasites than House Sparrows in Europe (Dobson & May 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation